First-principles insights of na-decorated B7N5 monolayer for advanced hydrogen storage - Liu, Zizhong; Chen, Xihao; Liao, Yuehong; Zhang, Longxin; Laranjeira, José A.S. [UNESP] (Elsevier, 2025)
Hydrogen is a versatile energy source, emerging as a promising alternative to traditional fossil fuels. Recently, two-dimensional (2D) materials have gained significant attention. Among these, new stable B7N5 monolayer have been discovered, demonstrating promising optical properties and enhanced absorption. In this context, our study explores the potential of Na decoration on B7N5 for hydrogen storage using density functional theory (DFT) simulations. The Na@B7N5 system can be saturated with up to 32 H2 molecules, showcasing an impressive gravimetric capacity of 7.70 wt%. Ab initio molecular dynamics (AIMD) simulations at 200 K and 300 K indicate fast desorption dynamics and reversible hydrogen storage. At the same time, the system retains its structural integrity at 290 K and pressures above 10 bar, making it an ideal substrate for H2 storage.
Keywords: Boron nitride; Energy; Hydrogen; Na-decorated; Reversible storage